Adaptive group-blind multiuser detection based on a new subspace tracking algorithm. - Reynolds, D.
Wang and Host-Madsen (see IEEE J. Select. Areas Commun., vol.17, p.1971-84, 1999) developed group-blind multiuser detectors for use in code-division multiple-access (CDMA) uplink environments in which the base station receiver has the knowledge of the spreading sequences of all the users within the cell, but not that of the users from other cells. Yu and Host-Madsen (see Proc. IEEE Vehicular Technology Conf. (VTC99), Houston, TX, p.1042-46, 1999) later developed an adaptive version of this detector for synchronous CDMA channels. We develop a new low-complexity, high-performance subspace tracking algorithm and apply it to adaptive group-blind multiuser detection in asynchronous multipath CDMA channels. The detector can track changes in the number of users and their composite signature waveforms. We present steady-state performance as well as the ability of the receiver to track changes in the signal subspace. We also address the performance gain of the group-blind detector over its blind counterpart for this application
Keywords: CDMA uplink environments; Adaptive group-blind multiuser detection; Asynchronous multipath CDMA channels; Base station receiver; Blind detector; Cellular radio; Code-division multiple-access.; Composite signature waveforms; High-performance subspace tracking algorithm; Low-complexity subspace tracking algorithm; Performance gain; Receiver; Signal subspace; Spreading sequences; Steady-state performance; Subspace tracking algorithm; Synchronous CDMA channels